Does self-harm have the desired effect?: comparing non-suicidal self-injury to high-urge moments in an ambulatory assessment design - Störkel, Lisa M.; Niedtfeld, Inga; Schmahl, Christian; Hepp, Johanna (Behaviour research and therapy, 2023)
All theoretical models of non-suicidal self-injury (NSSI) posit that regulation of negative affect (NA) is a central motive for NSSI, and cross-sectional work supports this. However, previous ambulatory assessment (AA) studies that examined NSSI found mixed results. We investigated the affect regulation function of NSSI in 51 women with DSM-5 NSSI disorder in a 15-day AA study with five random daily prompts and self-initiated NSSI prompts. We extend previous work by i) comparing NSSI moments to moments of a high-urge for NSSI, ii) adding high-frequency sampling following NSSI and high-urge moments, and iii) including tension as a dependent variable. We hypothesized that NA and tension would show a steeper decrease following NSSI than following high-urge moments, if NSSI was effective in reducing NA and tension. Results showed that the significant linear NA decline following NSSI was not steeper than that following high-urge moments. For aversive tension, we found that NSSI was associated with a significant linear decrease in tension, whereas resisting an urge was not. High-urge moments were better described by an inverted U-shaped pattern, likewise leading to decreased NA and tension following the reported urge. In exploratory analyses, we provide visualized clustering of the NA and tension trajectories surrounding NSSI using k-means and relate these to participants’ self-rated effectiveness of the NSSI events. Findings indicate that resisting an urge may also be effective in managing NA and tension and underline the utility of interventions such as urge-surfing.
Online verfügbar 2 Februar 2023, Artikelversion 8 Februar 2023
Gesehen am 28.03.2023